An Analysis of the Change in the Attitudes and Behaviors of Users before and after the Pandemic: Case Study; Ankara Çubuk-1 Dam - Sertaç Güngör; Elif Nur Doğan (Turkish Journal of Agriculture: Food Science and Technology)
During the pandemic process that has been going on for more than a year since the pandemic period was declared in 2020, the troubles and restrictions faced by people negatively affect the morale motivation of people. In this study, the definition of recreation areas, which are the leading places where people feel happy and peaceful, has been defined, what they contain is mentioned, and the adequacy of the recreational areas has been discussed in the survey and it has been determined that they are one of the most important needs in the cities. In the example of the recreation area of Çubuk-1 dam, it was investigated whether there is a change in the attitudes and behaviors of people before and after the pandemic, not face to face due to the pandemic, but through a voluntary survey based on social media. Although individuals thought that it was crowded after the pandemic, they preferred to use the recreation area of Çubuk-1 dam by paying attention to mask, distance and hygiene rules. The positive effects of physical activity, socialization, and outdoor travel on health are generally accepted by individuals. During the pandemic process, it has been observed that people have changed the way they spend their free time and the places they want to be, as they are overwhelmed by staying in their homes due to the prohibitions. The psychological and physical positive effects of recreation areas on human health and the changes caused by the pandemic in people's attitudes and behaviors paralleled the responses of the participants to the questionnaire.